2018
DOI: 10.1111/phn.12396
|View full text |Cite
|
Sign up to set email alerts
|

Revising a conceptual model of partnership and sustainability in global health

Abstract: The revised conceptual model embodies a more comprehensive model of global health partnerships with representation of nurses from low- and middle-resource countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…et al [ 104 ] Leffer’s Conceptual Framework for Partnership and Sustainability To assess equitable partnerships between global partners to address areas of shared importance, such as equity and justice in health promotion Dominican Republic Nursing Education 62. Upvall et al [ 105 ] Leffer’s Conceptual Framework for Partnership and Sustainability The purpose of this study was to revise a conceptual model of global health partnerships and collaboration integrating the perspectives of nurses from low- and middle-resource countries Multiple Countries Nursing Education 63. Van Acker et al [ 106 ] Level of Institutionalisation Scale To explore the extent to which the ‘10,000 Steps’ was integrated within the culture of organizations Belgium Primary Care 64.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…et al [ 104 ] Leffer’s Conceptual Framework for Partnership and Sustainability To assess equitable partnerships between global partners to address areas of shared importance, such as equity and justice in health promotion Dominican Republic Nursing Education 62. Upvall et al [ 105 ] Leffer’s Conceptual Framework for Partnership and Sustainability The purpose of this study was to revise a conceptual model of global health partnerships and collaboration integrating the perspectives of nurses from low- and middle-resource countries Multiple Countries Nursing Education 63. Van Acker et al [ 106 ] Level of Institutionalisation Scale To explore the extent to which the ‘10,000 Steps’ was integrated within the culture of organizations Belgium Primary Care 64.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, studies were undertaken within one country, but a small proportion (4%, 3/68) took place across multiple countries. While multiple study designs were found, qualitative methods were the most common, with 59% (40/68) of the studies employing methods such as interviews, focus groups and participant observation; this included four case studies [ 52 , 54 , 110 , 112 ], two grounded theory approaches [ 59 , 105 ] and one ethnography [ 85 ]. In total 28% (19/68) were mixed-method studies and 13% (9/68) were quantitative study designs using questionnaires, regression analyses or weighted scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While institutions and policies provide a foundation for building partnerships, fostering relationships and equitably engaging all stakeholders are the skills needed to promote long‐term sustainability. Engagement processes for building relationships include negotiating the roles and responsibilities of all partners, developing trust before proceeding with the partnership, and entering into the partnership in a spirit of collaboration (Upvall & Leffers, , ). Deliberately working to eradicate potential power differentials among partners and focusing clear attention to the contextual effects of diverse geopolitical factors help to firmly ground the partnerships and can lead to collaborations that extend beyond the given project or program (Upvall & Leffers, ).…”
mentioning
confidence: 99%
“…The entire collection of 31 published manuscripts from the Research Topic (RT) represent perspectives, community case study, curriculum, instruction and pedagogy, and evaluation types across academic, non-governmental organization and other global partnership forms. While every manuscript included in this RT addresses partnerships, the 18 manuscripts published as Part I of this e-book strongly exemplify partnership elements of collaboration, mutual planning, and capacity building ( 1 3 ) while those in Part II are more specific to programs and short term educational offerings.…”
mentioning
confidence: 99%